Sexual dimorphism of the incidence of significant relationships between selected parameters of feet and characteristics of trunk in adolescents aged 14 - 18 years - Mirosław Mrozkowiak; Marek Sokołowski; Marek Posłuszny; Alicja Kaiser (Kazimierz Wielki University, 2018)
Summary Introduction. Symmetry, asymmetry, mutual relationships and concomitance have become a subject of interest of numerous researchers. The analysis of the findings obtained in the own study conducted among adolescents aged 14-18 years revealed an incidental nature and randomness of the distribution of significant correlations in each age and gender range, which made it impossible to show any regularities or dependencies between the measured parameters. Material and method. The examinations carried out in the group of teenagers aged 14 to 18 years recorded 2,343 observations, including 1,148 girls and 1,195 boys, concerning the size of 89 parameters describing trunk and feet. The station for an assessment of selected features using the photogrammetric method consisted of a computer, a card, software, a display monitor, a printer and a projection-reception device with a camera.     Findings 1. The number of feet parameters revealing significant relationships with trunk parameters which differentiated the female gender from the male one was greater; likewise, the features in women revealed a more frequent relationship. Additionally, female sex was differentiated by morphological traits, the abnormal positioning of toes and the longitudinal arch of feet. 2. The number of trunk parameters correlating with foot parameters was observed to be bigger in the female gender than in the male one. The parameters in female subjects showed more relationships and the parameters which differentiated female sex included the frontal plane and the sagittal plane to a lesser extent, whereas male gender was characterized by the sagittal plane.